Sustainability in Fast Fashion: A Study on the Understanding of Youth Consumers - Jea Malig-on; Karl Campos (Inclusive Society and Sustainability Studies, 2024)
Fast fashion refers to the practice of imitating high-end designer apparel at a lower cost. The low cost of these apparels is achieved by using inferior and unsustainable materials and exploiting workers for long hours and low wages.  This study is about the awareness, buying intentions, and actions of students in Davao City about sustainability issues in the fast fashion sector. It aims to suggest innovative ways to change young consumers’ attitudes and behaviors toward sustainability in fast fashion. For the study, 5 participants are interviewed. The participants interviewed were chosen through purposive sampling. The participants are female 18-19 years old from varying socioeconomic backgrounds. Specifying the participants’ characteristics allows the researcher to gain an understanding of the relationship between consumer consciousness, purchase intentions, and behavior in the fast-fashion industry. The results show that young consumers have varying degrees of understanding about fast fashion and sustainability. This research shows that governments, fashion labels, and organizations interested in sustainable development can use this information to develop sustainable development plans. Public awareness can be improved to reduce youth unsustainability through effective policies, enabling various stakeholders to provide eco-friendly options when dealing with the problem. The generalizability of the results to a larger population can be improved by employing more diverse sample groups. Furthermore, utilizing different approaches and sampling strategies can increase the study's relevance and validate the findings.